Tren Global Penelitian Konseling Daring dan Kesehatan Mental di Era Digital: Analisis Bibliometrik 2015–2025 - Syarifah Rahmah (Universitas Muria Kudus, 2026)
This study aims to map global research trends on online counseling and mental health in the digital era using a bibliometric approach. Data were obtained from the Scopus database using the keywords